Pengaruh Lingkungan Kerja Fisik, Kepemimpinan dan Kompensasi Terhadap Loyalitas Karyawan Pada PT. Gino Valentino Bali - Wina Dwipayoga, Kadek Suhendra; Dewi Adnyani, I.G.A (E-Jurnal Manajemen; Vol 2 No 2 (2013), 2013)
This study aims to determine the physical work environment, leadership, compensation and simultaneously have a positive and significant impact on employee loyalty PT. Gino Valentino Bali. Respondents in this study amounted to 78 people by using census. This study tested the F test simultaneously and partially with t test. The results obtained were found positive and significant variables simultaneously between physical work environment, leadership, and compensation of employees' loyalty PT. Gino Valentino Bali. There is a positive and significant effect of the variable partial physical work environment, leadership, and compensation of employees' loyalty PT. Gino Valentino Bali. Of the three independent variables, namely variable physical work environment, leadership, and compensation, which predominantly affects employee loyalty to the PT. Gino Valentino Bali is a variable compensation   Key Word: physical work environment, leadership, compensation, employee loyalty